2013
DOI: 10.7322/jhgd.50392
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Caregivers of Patients With Cow’s Milk Allergy Regarding the Treatment

Abstract: Journal of Human Growth and Development 2013; 23(1): 58-64 ORIGINAL RESEARCH Resumo:Este estudo qualitativo teve como objetivo compreender as percepções de familiares de crianças e adolescentes com alergia à proteína do leite de vaca (APLV) em relação à doença e seu tratamento. Foram realizadas nove entrevistas e foi utilizado o método de análise de conteúdo. Surgiram três categorias com subcategorias: tratamento e educação do paciente e familiares (experiências vividas, base do tratamento e como lidar com a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…Table 2 summarizes the study characteristics. Most of the studies were conducted in Europe (the UK, Finland, Sweden and Denmark) (Akeson et al, 2007;Alanne et al, 2014;Alanne, Laitinen, Söderlund, & Paavilainen, 2012;Begen et al, 2018;Gallagher et al, 2012;Gunnarsson & Hydén, 2009;Lagercrantz et al, 2017;MacKenzie et al, 2015;Pitchforth et al, 2011;Rouf et al, 2012;Stjerna et al, 2014;Valentine & Knibb, 2011), some from the Americas (the US, Canada and Brazil) (Abdurrahman et al, 2013;Broome et al, 2015;Franciosi et al, 2012;Gillespie et al, 2007;Gupta et al, 2008;Harrington et al, 2015;Vargas et al, 2011;Yonamine et al, 2013) and two studies were conducted in Australia and New Zealand (Crowley et al, 2012;McBride et al, 2010). Several studies had mixed study populations and included parents and children across different age groups, see Table 2.…”
Section: Search Outcomementioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 summarizes the study characteristics. Most of the studies were conducted in Europe (the UK, Finland, Sweden and Denmark) (Akeson et al, 2007;Alanne et al, 2014;Alanne, Laitinen, Söderlund, & Paavilainen, 2012;Begen et al, 2018;Gallagher et al, 2012;Gunnarsson & Hydén, 2009;Lagercrantz et al, 2017;MacKenzie et al, 2015;Pitchforth et al, 2011;Rouf et al, 2012;Stjerna et al, 2014;Valentine & Knibb, 2011), some from the Americas (the US, Canada and Brazil) (Abdurrahman et al, 2013;Broome et al, 2015;Franciosi et al, 2012;Gillespie et al, 2007;Gupta et al, 2008;Harrington et al, 2015;Vargas et al, 2011;Yonamine et al, 2013) and two studies were conducted in Australia and New Zealand (Crowley et al, 2012;McBride et al, 2010). Several studies had mixed study populations and included parents and children across different age groups, see Table 2.…”
Section: Search Outcomementioning
confidence: 99%
“…Parents were also focused on living an ordinary life in relation to caring for an allergic child (Alanne et al, 2014;Yonamine et al, 2013), but they always had to plan and prepare for this (Lagercrantz et al, 2017;Stjerna et al, 2014). The home became a safe place (Pitchforth et al, 2011).…”
Section: Parental Rolesharing Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, toys are used both to satisfy the children's need for recreation and to enable their physical, mental, emotional and social development during hospitalization. 14,22,23 Diverse studies have shown that this technique enables children to become more cooperative with their treatment and able to express their feelings more effectively during hospitalization.…”
mentioning
confidence: 99%